If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15i + -4f + -17i + 3f = 0 Reorder the terms: -4f + 3f + 15i + -17i = 0 Combine like terms: -4f + 3f = -1f -1f + 15i + -17i = 0 Combine like terms: 15i + -17i = -2i -1f + -2i = 0 Solving -1f + -2i = 0 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '2i' to each side of the equation. -1f + -2i + 2i = 0 + 2i Combine like terms: -2i + 2i = 0 -1f + 0 = 0 + 2i -1f = 0 + 2i Remove the zero: -1f = 2i Divide each side by '-1'. f = -2i Simplifying f = -2i
| x-19.8=-4.24 | | 6cos(x)+8sin(x)=0 | | 3(2x-3)-13=2(x-1) | | 2n-16=14 | | 9u-v-11u+v= | | xt(-100)=-99 | | 6.2+1.2=8.9x | | ax+bx-3=-8 | | d-14.2=-18.7 | | 10y-5z-y-3z= | | (3x-2)(5x+1)(x)= | | k-4/=3 | | 6y+33=-x+3 | | (5.8+4)-(7.2-9)= | | 2t+3=7 | | 30-4x=14-8x | | 1.04x+3.14=7.89 | | 17+90+x=18 | | 12-5r-2+4r= | | 4+6n=6+2n | | 2x-3+4x+11= | | 12x+6=2y-4 | | w=z^7-3z^6+13 | | 20(v+4)-4v=4(4v+1)-11 | | 7c+4b+3b+a+10c-5a= | | 3g+2h-7g+9g= | | 19w=13.5 | | f(x)=x^3-3x^2-8x+30 | | 6(x+5)=3(2x+1)+27 | | 13=-3+4r | | 8d-6e+9e-5d= | | 2x+16=x+21 |